ANALISIS PERAN SEKTOR PERTANIAN DI KABUPATEN SUKOHARJO - NUNING SETYOWATI (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2012)
Economic development is identified by the structural transformation of the economy as quickly is of an economy that relies on agriculture into a modern industrial economy and the all-services complex. The study aims to identify the role of agriculture in the district of Sukoharjo by analyzing the performance, the ability of employment absorption and create job opportunities for other sectors. This research uses descriptive analytical method with a basis of primary data in the form of GrossRegional Domestic Product data and the amount of agricultural and non-agricultural sector labor in Sukoharjo district.